Expected features of the course leader in the rehabilitation healthcare professionals' higher education: A qualitative study on students' perspectives. - Benedetto Giardulli; Laura Furri; Marco Testa; Andrea Dell'Isola; Gianluca Bertoni; Simone Battista (PLoS ONE)
Course leaders in rehabilitation healthcare professionals' higher education face challenges stemming from multi-disciplinarity and the co-existence of different stakeholders. So far, the literature mainly attributed to course leaders' managerial tasks, neglecting other fundamental transversal skills. Students represent an essential source of information for understanding the expected characteristics and roles of course leaders in rehabilitation healthcare degree programmes. This study explored students' expected features of the course leaders in the rehabilitation healthcare professionals' higher education. A qualitative interview study was carried out. A group of recent graduates and students of the MSc in 'Healthcare Professionals Rehabilitation Sciences' (University of Verona, Verona, Italy) was recruited using purposive sampling. Data were analysed using 'Reflexive Thematic Analysis' by Braun & Clarke. Ten healthcare professionals agreed to partake in the study (age 30 ± 9; men N = 2; women N = 8). Five themes were generated from the analysis: 1) 'A Collaborative Manager', as students perceived course leaders as non-authoritarian managers who involved all the stakeholders in the decision-making process addressing aspects such as curriculum adjustments, program improvements, and any challenges faced; 2) 'A Diplomatic yet Honest Communicator', as students needed course leaders capable of communicating transparently; 3) 'A Flexible Mediator', as course leaders should actively listen to all stakeholders, mitigating conflicts; 4) 'An Empathic and Available Guide', as students need course leaders available and ready to help; 5) 'An Experienced Healthcare Professional', as students felt course leaders should have a clinical background related to the course they lead. The results of this study suggested that students expect the course leaders to have a wide range of qualities and attitudes about soft (i.e., adaptation, communication, organisation skills, teamwork) and hard skills (i.e., clinical experience, evidence-based practice updated). They expect a course leader to consider all stakeholders' needs and preferences to guarantee course harmony and satisfaction.